2017
DOI: 10.1016/j.scitotenv.2017.07.253
|View full text |Cite
|
Sign up to set email alerts
|

The profound effect of harmful cyanobacterial blooms: From food-web and management perspectives

Abstract: Sustainable and effective water management plans must have a reliable risk assessment strategies for harmful cyanobacterial blooms (HABs) that would enable timely decisions to be made, thus avoiding the trespassing of ecological thresholds, leading to the collapse of ecosystem structure and function. Such strategies are usually based on cyanobacterial biomass and/or on the monitoring of known toxins, which may, however, in many cases, under- or over-represent the actual toxicity of the HAB. Therefore, in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…This result showed that the ratios of phytoplankton to heterotrophic bacteria in the bloom (0.0410422) and edge sites (0.0483856), which was approximately twofold higher than in the control site (0.0910008). This result supports the previous result HAB redirects carbon and energy flow within the pelagic food-web toward heterotrophic bacteria-dominated processes, primarily through the inhibition of algal growth and enhancement of bacterial proliferation ( Šulčius et al, 2017 ). Since microbial ecosystems in aquatic environments are the result of complicated interactions between photosynthetic phytoplankton species and heterotrophic microorganisms ( Carrillo, Medina-Sánchez & Villar-Argaiz, 2002 ; Cole, 1982 ; Rooney-Varga et al, 2005 ), it is often necessary to analyze the phytoplankton community separate from the other bacterial species.…”
Section: Discussionsupporting
confidence: 92%
“…This result showed that the ratios of phytoplankton to heterotrophic bacteria in the bloom (0.0410422) and edge sites (0.0483856), which was approximately twofold higher than in the control site (0.0910008). This result supports the previous result HAB redirects carbon and energy flow within the pelagic food-web toward heterotrophic bacteria-dominated processes, primarily through the inhibition of algal growth and enhancement of bacterial proliferation ( Šulčius et al, 2017 ). Since microbial ecosystems in aquatic environments are the result of complicated interactions between photosynthetic phytoplankton species and heterotrophic microorganisms ( Carrillo, Medina-Sánchez & Villar-Argaiz, 2002 ; Cole, 1982 ; Rooney-Varga et al, 2005 ), it is often necessary to analyze the phytoplankton community separate from the other bacterial species.…”
Section: Discussionsupporting
confidence: 92%
“…Algal blooms have become a worldwide and challenging water pollution problem in freshwater ecosystems due to harmful algae that cause a gradual degeneration of the water’s self-purification function and decrease the source water quality [ 1 , 2 ]. In the past several decades, a growing number of studies concerning the environmental factors of algal bloom outbreaks and decline have been explored [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of cyanobacterial toxins, the presence of various microcystin (MC) analogues, anatoxin-a (ANTX-a) and nodularin (NOD) has been confirmed [7,9,12,13]. Reports on the detection of cyanopeptides in the Curonian Lagoon was also published [10,13].…”
Section: Introductionmentioning
confidence: 96%
“…Previous research in the Curonian Lagoon has only focused on the ecotoxicological assessment of cyanobacterial scum and cyanobacterial toxins from the perspective of the ecosystem and public health [7,[9][10][11][12][13]. To our knowledge, no published data on the biological activity of metabolites produced by cyanobacteria and eukaryotic microalgae occurring in this lagoon exist.…”
Section: Introductionmentioning
confidence: 99%